Kajian Alat Muat dan Alat Angkut untuk Optimalisasi Produksi Batu Andesit di PT Nurmuda Cahaya Kecamatan Batujajar Timur, Kabupaten Bandung, Provinsi Jawa Barat - Rahmat Widayat; Zaenal; Iswandaru (UNISBA Press, 2022)
Abstract. The condition of the large material has an effect on the circulation time of the digging tool. Based on the results of proven calculations that fragmentation of chunks caused the efficiency of the digging-fit tool is very low, namely 55.4% with actual production of 7,329 tons/month and resulted in a domino effect on the efficiency of the hauler of 55.3% and production of only 6,676 tons/month. So that the percentage of mechanical equipment production volume to blasting volume is 52.35%. Based on the results of the study of mechanical equipment production through the condition of the material, the problem solving will be done is by procurement of tools for fragmentation of chunks of rock. The recommended tool is the PC200-8M0 excavator breaker that will assist the process of material mining activities. After going through the calculation stage, the productivity capability of PC 200-8M0 excavator breaker reaches 1/4 of the theoretical volume of dig-fit equipment of 17 m3/h capable of producing as much as 225.2 tons /day of rock so that 5,856 tons can be solved during the month through only 1 excavator breaker tool. Based on the production calculation, 76.35% of the rock can be resolved by 1 excavator breaker which means that this tool is able to calculate the performance of the dig-fit tool to 70,56% so that the monthly production of PT Nurmuda Cahaya rocks can be met. Production engineering that has been calculated where the ability of excavator breaker equipment will produce rocks of 5,856 tons/month so that the efficiency of the dig-fit equipment will increase to 70.56% with productivity results of 84.3 tons/hour and transportation efficiency to 70.54% with a productivity value of 77.21 tons/hour. Abstrak. Kondisi material yang berukuran besar tersebut berpengaruh terhadap waktu edar alat gali-muat. Berdasarkan hasil perhitungan terbukti bahwa fragmentasi bongkah menyebabkan efisiensi alat gali-muat sangat rendah yaitu 55,4% dengan produksi aktual 7.329 ton/bulan serta mengakibatkan efek domino pada efisiensi alat angkut yaitu sebesar 55,3% dan produksi hanya sebesar 6.676 ton/bulan. Sehingga persentase volume produksi alat mekanis terhadap volume peledakan sebesar 52,35%. Berdasarkan hasil kajian produksi alat mekanis melalui kondisi material tersebut maka pemecahan masalah yang akan dilakukan ialah dengan pengadaan alat untuk pemecah/penghancur fragmentasi bongkah batuan. Alat yang direkomendasikan yaitu excavator breaker PC200-8M0 yang akan membantu proses kegiatan penambangan material. Setelah melalui tahap perhitungan, kemampuan produktivitas excavator breaker PC 200-8M0 mencapai ¼ dari volume teoritis alat gali-muat yaitu sebesar 17 m3/jam yang mampu menghasilkan produksi sebanyak 225,2 ton/hari batuan sehingga 5.856 ton dapat terpecahkan selama bulan tersebut hanya melalui 1 alat excavator breaker. Berdasarkan hasil perhitungan produksi tersebut maka 76,35% batuan dapat teratasi oleh 1 breaker excavator yang artinya alat ini mampu mengefesiensikan kinerja alat gali-muat menjadi 70,56% sehingga produksi bulanan batuan PT Nurmuda Cahaya dapat terpenuhi. Rekayasa produksi yang sudah diperhitungan dimana kemampuan alat excavator breaker akan memproduksi batuan sebesar 5.856 ton/bulan sehingga efisiensi alat gali-muat akan meningkat menjadi 70,56% dengan hasil produktivitas 84,3 ton/jam serta efisiensi alat angkut menjadi 70,54% dengan nilai produktivitas 77,21 ton/jam.